Reading Orosius in the Viking Age: An influential yet problematic model - Lucrezia Pezzarossa (Filologia Germanica, 2024)
This paper considers the representation of war in the Old English Orosius, in order to investigate what models the Late Antique text might have provided to its English audience at the time of the Viking invasions. In particular, the present analysis seeks to highlight how, in that specific context, Orosius’ work – and especially the vernacular rendering of the sack of Rome of AD 410 – might have raised serious questions about the workings of history.